2009
DOI: 10.1083/jcb.200809008
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase is required for radial sorting of axons and Schwann cell remyelination in the peripheral nervous system

Abstract: During development, Schwann cells (SCs) interpret different extracellular cues to regulate their migration, proliferation, and the remarkable morphological changes associated with the sorting, ensheathment, and myelination of axons. Although interactions between extracellular matrix proteins and integrins are critical to some of these processes, the downstream signaling pathways they control are still poorly understood. Integrin-linked kinase (ILK) is a focal adhesion protein that associates with multiple bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
133
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 55 publications
10
133
0
Order By: Relevance
“…Of great interest was how ILK modulated these molecules. It has been shown that the expression of ERCC1 (Li et al, 2012) and GST-π (Zhang et al, 2009) is regulated by MAPK/ ERK pathway, and the RhoE has a direct interaction with ILK (Pereira et al, 2009;Berti et al, 2011). The western blotting results confirmed that the phosphorylation of ERK was attenuated by ILK silencing, which might result in the negative regulation of ERCC1 and GST-π.…”
Section: Discussionsupporting
confidence: 63%
“…Of great interest was how ILK modulated these molecules. It has been shown that the expression of ERCC1 (Li et al, 2012) and GST-π (Zhang et al, 2009) is regulated by MAPK/ ERK pathway, and the RhoE has a direct interaction with ILK (Pereira et al, 2009;Berti et al, 2011). The western blotting results confirmed that the phosphorylation of ERK was attenuated by ILK silencing, which might result in the negative regulation of ERCC1 and GST-π.…”
Section: Discussionsupporting
confidence: 63%
“…Downregulation of the protein results in loss of phosphorylation of the putative substrate(s) and the biological response This has been shown extensively through small interfering RNA (siRNA)-mediated knockdown of ILK protein and gene ablation (reviewed by McDonald et al (2008a)). For example, ablation of ILK was associated with loss of Akt phosphorylation on Ser-473 White et al, 2006;Wang et al, 2008;Pereira et al, 2009). On the other hand, ILK depletion in vascular smooth-muscle cells was actually associated with hyper-phosphorylation of MLC-20 (Kogata et al, 2009;Montanez et al, 2009), although this could be because of compensation by other kinases capable of phosphorylating MLC-20, such as Rho-associated kinase (Amano et al, 1996) or zipper-interacting protein kinase (Murata-Hori et al, 1999;Niiro and Ikebe, 2001).…”
Section: Does Ilk Fulfill the Biochemical And Biological Criteria Shomentioning
confidence: 83%
“…Schwann cell-specific inactivation of the genes coding for b1-integrin, Rac1, and integrin-linked kinase (ILK) were similarly found to cause radial sorting defects whereas inactivation of the genes coding for b4-integrin and dystroglycan (both proteins are expressed late in nerve development) were found to be important for myelin stability and nodal morphogenesis (Feltri et al 2002;Benninger et al 2007;Nodari et al 2008;Pereira et al 2009). An evolving but incomplete model holds that laminin (or basement membrane) ligation of b1 integrins promotes lammellipodial extension and axonal interdigitation through alterations of the activated state of Rac1, Cdc42 and Rho/ Rho kinase.…”
Section: Peripheral Nerve Axonal Envelopment and Myelinationmentioning
confidence: 99%